(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article describes the conditions for the selection of the head and teacher of the subject of initial training before the call-up (military training before the call-up), their obligations and today’s requirements for them. The military-patriotic educational work carried out by the head of the military training subject and the teacher during extracurricular time with the students in the military-patriotic spirit was highlighted.